IDENTIFIKASI GOLONGAN SENYAWA ANTIHIPERGLIKEMIK Caesalpinia globulorum Bakh. f. & Van Royen PADA TIKUS PUTIH (Rattus norvegicus L.) HIPERGLIKEMIA - , DESY MARTIANA SARI; , Prof. Sukarti Moeljopawiro, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Caesalpinia globulorum Bakh. f. & Van Royen is an original plant in Buton island, South east Sulawesi. The benefits of this plant are known rarely by local people, whereas this plant has potential as a herbal medicine. In India Caesalpinia bonducella have used as antihyperglycaemia. Therefore the objective of this study was to identify antihyperglycaemic compound of Caesalpinia globulorum Bakh. f. & Van Royen on hyperglycaemia rat. The Caesalpinia globulorum Bakh. f. & Van Royen seeds were collected from Buton island. Hyperglycaemia rats (Rattus norvegicus L.) male, wistar were used in this study. The hyperglycaemia rat were made by injecting glucose monohydrate 1,35 mg/kg BB. The seed was extracted using ethanol, to detect the effectiveness of ethanolic extract, 200 mg/kg BB extract were given to hyperglycaemia rat using two methods. They were preventive method (exstract were given at initial treatments) and curative method (exstract were given at 45 th minutes). Ethanolic extract of Caesalpinia globulorum Bakh. f. & Van Royen seed was triturated by n-heksan. The yield of trituration were liquid fractions and solid fractions. The effectiveness of both fractions were detected using the same method as in the extract detection. Both of an extract and fractions were analyzed using thin layer chromatography followed by application of various detection reagents for identification of compounds. The results showed that the extract given to the preventive group lowered blood glucose level significantly compared with other groups. The extract (in preventive group) had the lowest AUC0-300 was 4085,5 and the highest percentage of lowering blood glucose (10,75%). The effectiveness of liquid fractions showed that at the preventive group the AUC0-300 was 4526,32 and the percentage of lowering blood glucose was -14,46 %. The AUC0-300 of liquid fraction in curative group was 4194,17 and the percentage of lowering blood glucose was -3,59 %. While the AUC0-300 of solid fraction (in preventive group) was 4585,72 and the percentage of lowering blood glucose was -16,35 % and the AUC0-300 in curative was 4472,87 and the percentage of lowering blood glucose was -13,05 %. The glibenklamid group had the lowest AUC0-300 was 3659,47 and the highest percentage of lowering blood glucose was 12,77%. The identification of antihyperglycaemic compound showed that both either extract or fraction was terpenoid. It could be concluded that the antihyperglycaemic compound on hyperglycaemia rat, in the ethanolic extract of the seed of Caesalpinia globulorum Bakh. f. & Van Royen was terpenoid which has a few conjugated double bonds.